How do you differentiate f(x)=xsinx using the product rule?

2 Answers

hi
PRODUCT RULE SAYS
if to diffrentiate "uv"( here i will take w.r.t to x)
i.e
d((uv))/dx=u*d(v)/dx+v*du/dx
i.e u must know
diffrentiation of x^n=nx^(n-1)
here..,

**diffrentiation of x=(1)x^(1-1) =1

diffrentiation of" sinx" is "cos x "

NOW,
dx.sin(x)/dx=(x).dsin(x)/dx+(sinx)(d(x)/dx) = xcos(x)+sin(x)
=
So diffrentiation of F(X)=x sin(x)-=x cos(x)+sin(x)

Nov 12, 2017

f'(x)=xcosx+sinx

Explanation:

"given "f(x)=g(x)h(x)" then"

f'(x)=g(x)h'(x)+h(x)g'(x)larrcolor(blue)"product rule"

g(x)=xrArrg'(x)=1

h(x)=sinxrArrh'(x)=cosx

rArrf'(x)=xcosx+sinx